2022
DOI: 10.54905/disssi/v26i119/ms41e2003
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Septal defect (VSD) as an extra renal manifestation in Congenital Anomalies of Kidney and Urinary Tract (CAKUT) Syndrome: A rare Case report

Abstract: Congenital abnormalities of the kidney and urinary tract (CAKUT) are a key cause of morbidity and a substantial contributor to end-stage renal disease (ESRD). These anomalies are the most prevalent form of birth malformation.Other system abnormalities such as those of the heart, gastrointestinal tract, central nervous system, skeletal system, respiratory system, facial dysmorphism, reproductive system, abdominal wall coexist with these anomalies. Congenital heart defects (CHD) are the most frequent complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Overall, we found significantly more extra-renal/cardiac malformations in our patients with both CAKUT and CHD than has been reported with either CAKUT or CHD alone ( 7 , 8 , 31 ). These findings may be related to the high rate of genetic syndromes identified in this study, with 13 of our 14 genetic diagnoses (93%) herein related to a previously identified syndrome.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Overall, we found significantly more extra-renal/cardiac malformations in our patients with both CAKUT and CHD than has been reported with either CAKUT or CHD alone ( 7 , 8 , 31 ). These findings may be related to the high rate of genetic syndromes identified in this study, with 13 of our 14 genetic diagnoses (93%) herein related to a previously identified syndrome.…”
Section: Discussionsupporting
confidence: 46%
“…Previously CAKUT and CHD have both been found as solitary anomalies or co-existing with other organ system malformations ( 3 , 4 , 7 , 8 , 27 31 ). Overall, 40%–60% of patients with a CAKUT or CHD have an additional extra-renal or extra-cardiac abnormality ( 7 , 8 , 27 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case, no such abnormality was detected on the ultrasound abdomen and pelvis, which made this case an isolated KFS without any association with other syndromes, making this a unique case that could have been underdiagnosed. Various cardiac and renal manifestations are associated with KFS, which changes the type as per the various classifications and, hence, the management [7].…”
Section: Discussionmentioning
confidence: 99%